Property in human biomaterials: a new methodology - Douglas, S; Goold, I (Cambridge University Press, 2016)
In disputes over the use and possession of the human body and its parts, there has been a marked reliance on property law concepts. Judges frequently resort to the language of “ownership”, “gifts”, “donations”, “trusts” and so on, in order to resolve disputes over the use of human biomaterials. When this happens, however, we observe certain recurring mistakes. Judges and academics writing in this area have sometimes misunderstood the basic rules governing the creation and operation of property rights. We do not seek to take a stance on the normative matters at stake. Our aim is to provide an accurate account of how property law could operate when applied in the context of human tissue use. We hope to redress some misconceptions, but our bigger goal is to provide a new methodology of how to work through the various questions that must be considered when determining how to regulate human tissue, by explaining how property principles would work at each stage. In this way, we seek to enable those who wish to debate whether property principles should be applied to human tissue the means to have accurate debates.